Extraction of gaharu oil using enzymatic hydrodistillation - Muhamad Khairul Kahfi, Abdullah (2008)
Gaharu is one of the most precious trees in the world and its essential oil is one of the most expensive natural products existing today. The main uses of gaharu essential oil are in medicinal, perfumery and incense. Grade C gaharu from peninsular Malaysia was used in this study. Previous method of hydrodistillation is not effective, yield of gaharu essential oil is relatively small and consumes a lot of time. This study of extraction of gaharu essential oil using enzymatic hydrodistillation was developed to improve the previous method. The parameters that are manipulated in this study are solid to solvent ratio and pretreatment time to achieve the optimum yield of essential oil. From the study, gaharu essential oil that extracted using enzymatic hydrodistillation produce highest yield at lowest solid to solvent ratio and highest pretreatment time. Based on the results, it was found that the ratio 1:8 give 0.1092% yield which is the highest yield compare to yield at 1:12, 1:16 and 1:20 solid to solvent ratio. For pretreatment time, the highest yield of extracted oil occurs at nine hours of pretreatment time which is 0.1375%. This study had proved that the parameter, solid to solvent ratio and pretreatment time are suitable in optimizing the yield of essential oil.